2015
DOI: 10.1111/1365-2745.12445
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the heritable and plastic components of the competitive and facilitative effects of an alpine foundation species

Abstract: Summary1. Differences in effects between phenotypes of foundation species on subordinate species have been reported, but no study has separated their heritable and plastic components. In a subalpine community of the French Pyrenees, we observed two phenotypes of Festuca gautieri: tight cushions in dry convex outcrops with few subordinate species and loose cushions in wet concave slopes with many subordinate species, suggesting differences in effects of the two phenotypes on subordinates. 2. Using two reciproca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 67 publications
2
27
1
Order By: Relevance
“…Forage nutrient value is likely a balance of heritable and environmentally plastic variation (Santis and Chiaravalle ; Al Hayek et al . ). All plants sampled before the watering treatments were imposed exhibited similarly high nutrient value.…”
Section: Discussionmentioning
confidence: 97%
“…Forage nutrient value is likely a balance of heritable and environmentally plastic variation (Santis and Chiaravalle ; Al Hayek et al . ). All plants sampled before the watering treatments were imposed exhibited similarly high nutrient value.…”
Section: Discussionmentioning
confidence: 97%
“…This is in line with previous reports showing differences in facilitation effects on the subordinate community composition between different phenotypes of the same species (e.g., Michalet et al., ; Schöb et al., ). However, in contrast to such reports, we do not have evidence that our two C. galianoi phenotypes occupy different topographical microhabitats that could have selected for different genotypes (e.g ., Al Hayek et al., and Michalet et al., ). We suggest that differences between phenotypes, and parallel changes in subordinate communities, were therefore due to differences in shrub age (i.e., shrub ontogeny).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies in alpine systems have documented contrasting effects of different phenotypes of foundation species on subordinate species (Al Hayek, Maalouf, Touzard, & Michalet, ; Al Hayek, Touzard, Le Bagousse‐Pinguet, & Michalet, ; Al Hayek et al., ; Bonanomi et al., ; Michalet, Maalouf, & Hayek, ; Michalet et al., ). However, the mechanisms underlying these effects are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time and at each site, cushions of T. caespitosum become more convex and tighter from the more sheltered and mild loose habitat to the more exposed and stressful tight habitat, as observed for other alpine cushion species displaying similar phenotypic differentiation between loose and tight phenotypes (Michalet et al , Al Hayek et al , ). Cross‐transplantation experiments and reciprocal common‐gardens allow disentangling environmental plasticity effects from heritable effects, which are both likely to be involved in such phenotypic differentiation along small‐ or large‐scale environmental gradients (Al Hayek et al ). However, because most alpine cushion plants are too slow‐growing to be tested in such design, Al Hayek et al () proposed that a consistency of phenotypic effects observed along climate stress gradients suggests a likely heritability of phenotypic differentiation occurring at small scale.…”
Section: Discussionmentioning
confidence: 99%